2008
DOI: 10.1007/s11249-008-9329-y
|View full text |Cite
|
Sign up to set email alerts
|

The Tribological Properties of Ionic Liquids Composed of Trifluorotris(pentafluoroethyl) Phosphate as a Hydrophobic Anion

Abstract: The tribological properties of trifluorotris(pentafluoroethyl) phosphate [(C 2 F 5 ) 3 PF 3 -, FAP]-derived ionic liquids were evaluated under boundary conditions. The anion is hydrophobic in comparison with bis(trifluoromethylsulfonyl)imide [(CF 3 SO 2 ) 2 N -, TFSI]. 1,3-Dialkyli midazolium salts of FAP provided much lower friction than 1,3-dialkylimidazolium salts of TFSI. In addition, the FAP salts exhibit better anti-wear properties than the TFSI salts. Another advantage of the FAP anion is availability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
105
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(112 citation statements)
references
References 26 publications
(43 reference statements)
1
105
1
Order By: Relevance
“…Accordingly good antiwear properties, hydrolytic stability and hydrophobicity of the [NTf 2 ] anion reported by Minami et al [16,30]. This paper studies the effectiveness of using two ionic liquids …”
Section: *Manuscript Click Here To View Linked Referencesmentioning
confidence: 89%
See 1 more Smart Citation
“…Accordingly good antiwear properties, hydrolytic stability and hydrophobicity of the [NTf 2 ] anion reported by Minami et al [16,30]. This paper studies the effectiveness of using two ionic liquids …”
Section: *Manuscript Click Here To View Linked Referencesmentioning
confidence: 89%
“…Material pairs such as steel/steel, steel/SiO 2 , steel/aluminium, steel/copper, steel/Si(100), steel/sialon, steel/titanium, sialon/Si 3 N 4 and steel-PVD coatings (TiN, DLC and CrN) have been explored using pyridinium, imidazolium, phosphonium or ammonium as cation combined with anions such as hexafluorophosphate (PF 6 ), tetrafluoroborate (BF 4 ), CF 3 SO 3 , (C 2 F 5 ) 3 PF 3 (or FAP) and (CF 3 SO 2 ) 2 N (or NTf 2 ) [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. The most common anions examined in the tribology literature are BF 4 and PF 6 , but their hydrolytic instability and tendency to produce corrosive HF have been reported [27].…”
Section: *Manuscript Click Here To View Linked Referencesmentioning
confidence: 99%
“…Despite their good tribological behaviour, the hydrolysis products of those anions are highly corrosive [36]. This fact provoked the introduction of new and more stable ILs based on [FAP] and [NTf 2 ] anions [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53], which present enhanced tribological properties due to the formation of fluoride tribofilms, especially at high loads [54]. Recently, phosphonium cation-based ILs have been introduced in this field because of their growing commercial availability and good tribological performance [26,[55][56][57][58][59][60][61][62].…”
Section: Introductionmentioning
confidence: 99%
“…Since then, there have been numerous reports on similar applications have been published in international tribology journals. Thus far, the relationship between the chemical structure and the tribological properties of RT-ILs has been fundamentally studied [9][10][11]; it has been observed that hydrophobic anions (e.g., TFSA) afforded better tribological properties to RT-ILs than the hydrophilic anions (e.g., BF 4 ) [12,13]. Higher alkyl groups in imidazolium cations are instrumental in improving the tribological properties of a compound.…”
Section: Introductionmentioning
confidence: 99%
“…To date, there are brief reports on the tribological properties of R 4 P-derived RTILs [13,[20][21][22][23][24][25]. In this work, we focused on the relationship between the chemical structure and tribological properties of RT-ILs.…”
Section: Introductionmentioning
confidence: 99%